Morocco : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2004)
This 2004 Article IV Consultation highlights that Morocco's macroeconomic conditions remained strong in 2003. Growth increased to 5.5 percent because of an exceptionally good cereal production, while non-agricultural growth showed signs of revival. Inflation was below 2 percent and the external position strengthened further. External reserves reached the equivalent of 10 months of imports of goods and services and covered the totality of external public and publicly guaranteed debt. Macroeconomic conditions are projected to remain broadly unchanged in 2004.